Motor Learning and Physical Exercise in Adaptive Myelination and Remyelination. (May 2022) - Bloom, Mara S.; Orthmann-Murphy, Jennifer; Grinspan, Judith B.
The idea that myelination is driven by both intrinsic and extrinsic cues has gained much traction in recent years. Studies have demonstrated that myelination occurs in an intrinsic manner during early development and continues through adulthood in an activity-dependent manner called adaptive myelination. Motor learning, the gradual acquisition of a specific novel motor skill, promotes adaptive myelination in both the healthy and demyelinated central nervous system (CNS). On the other hand, exercise, a physical activity that involves planned, structured and repetitive bodily movements that expend energy and benefits one's fitness, promotes remyelination in pathology, but it is less clear whether it promotes adaptive myelination in healthy subjects. Studies on these topics have also investigated whether the timing of motor learning or physical exercise is important for successful addition of myelin. Here we review our current understanding of the relationship of motor skill learning and physical exercise on myelination.